Biomass gasification, pyrolysis, and torrefaction practical design, theory, and climate change Mitigation - Basu, Prabir; Kaushal, Priyanka (Cambridge, Massachusetts Academic Press, 2023)
"Biomass Gasification, Pyrolysis, and Torrefaction: Practical Design, Theory, and Climate Change Mitigation, Fourth Edition explores the role of biomass conversion in climate change mitigation. With a focus on design, analysis and operational aspects of biomass gasification, pyrolysis and torrefaction, this edition offers comprehensive coverage of biomass in its gas, liquid and solid states. Processing and cleaning of product gas in gasification is considered, as are biomaterials and their development, making this a versatile resource that not only explains the basic principles of energy conversion systems, but also provides valuable insights into the design of a complete biomass conversion systems. For the first time, hydrogen production for fuel cells applications is addressed, reflecting the expanding role of hydrogen as a fuel source. Although the book carries the name ‘biomass’, the bulk of its content is also applicable to non-biomass fuels like coal, petcoke, municipal solid waste and others. This book will allow professionals, such as engineers, scientists, and operating personnel of biomass gasification, pyrolysis or torrefaction plants, to gain a better comprehension of biomass conversion."
Includes bibliographical references and index.
Keywords: Biomass energy; Biomass gasification; Climate change mitigation; Pyrolysis; Renewable energy sources -- Environmental aspects